Charismatic Leaders, Tribal Coalition and State Formation: The Historical Sociology of State Establishment in Pre-modern Iran - Hojjat Kazemi (دولت‌پژوهی, 2022)
The main objective of this article is to describe and analyze the mechanism of establishment of the Iranian States between the Seljuks' formation and the Qajar dynasty's end. The article is based on a critique of the two theories of Oriental Despotism and Orthodox Marxism; It seeks to provide a different perspective to explain the process of establishing the state in Iran by using Ibn Khaldoun's discussions about the conflict between primitive and Civilized communities. Based on this, the article believes that the pattern of state establishment in traditional Iran will be understood when this process is placed in the context of the fundamental conflict of Iranian history between tribal groups and sedentary communities. With such a basis, the article's point of view is that the model of the establishment of the traditional state should be analyzed in terms of the centrality of tribes as state-building actors. The findings of the article show that among the multitude of tribes inside and outside the Iranian plateau, some tribes, due to the emergence of charismatic leaders among them, succeeded in overcoming the division inherent in tribal life and forming a coalition that was the product of a "great Asabiyyah". Conquering through force and compromising through the promise of sharing in the spoils were two central factors in the joining of the tribes to this coalition. Charismatic leaders took the great Asabiyyah in the tribal alliance beyond the limited attitude of scattered looting and turned it towards conquering different regions. This process established the initial and unstable form of the tribal state, one that becomes an imperial state in its next evolution.